A Study on Key Retailing Strategies of Carrefour and Its Intervention Plan During the Pandemic (Covid-19): UAE (European Journal of Marketing and Economics, 2023)
An economy is governed by its markets and for a growing economy retailing is a blooming industry. The secret of successful retailing is to give the customers what they want. Keeping this in mind a French Retailer, ‘CARREFOUR’ is progressing high across various nations of the world keeping in mind the cross national and demographic styles of various countries. It adapts itself with the form and culture of every nation and penetrates deep though its roots. The pandemic of COVID-19, gave carrefour an immense exposure of the new marketing plans which rescued it and gave it a new strategic insight. The scope of this paper is to study key strategies of this retail giant in Dubai (UAE). This paper also focuses on the various strategies adopted by this retail joint keeping in mind the complete marketing mix and adoption of the new era of online shopping post the pandemic time.
Keywords: Retailing, marketing mix, one stop shopping, consumer and product centric, online and DSF